New regionalisms in the global political economy - Breslin, Shaun; Christopher W. Hughes; Phillips, Nicola; Rosamond, Ben. (Oxford: Taylor and Francis Group, 2002)
Following the financial crisis at the end of the twentieth century, regionalisms in the global political economy have evolved in a number of ways. This informative book brings together the leading scholars in the field to provide cutting edge analyses of contemporary regions and regionalist projects.
Includes bibliographical index.
osa;07/09/2016
Loans
Keywords: International economic integration; Regionalism; Globalization; International economic relations; Regionalism - case studies